2010
DOI: 10.1155/2010/858094
|View full text |Cite
|
Sign up to set email alerts
|

BacMam Virus Transduced Cardiomyoblasts Can Be Used for Myocardial Transplantation Using AP-PEG-A Microcapsules: Molecular Cloning, Preparation, andIn VitroAnalysis

Abstract: The potential of genetically modified cardiomyoblasts in treating damaged myocardium is well known. However, efficient delivery of these cells is of major concern during treatment. The limiting factors are the massive cell death that occurs soon after their intramyocardial transplantation into the beating heart. To address these problems, we generated recombinant baculoviruses (BacMam viruses) which efficiently transduced cardiomyoblast cells under optimized conditions. These genetically modified cells were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In vitro analysis showed that Bac-NP-transduced cells were able to express their transgene for at least 3 weeks (Figure 2C), which is comparable to other experimental results. 24,31 This temporal expression of the delivery system is beneficial in many cases, particularly for angiogenesis where the expression of the therapeutic protein ceases once its job is done. Further studies need to be done to comprehend the exact mechanism of such a gene delivery system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro analysis showed that Bac-NP-transduced cells were able to express their transgene for at least 3 weeks (Figure 2C), which is comparable to other experimental results. 24,31 This temporal expression of the delivery system is beneficial in many cases, particularly for angiogenesis where the expression of the therapeutic protein ceases once its job is done. Further studies need to be done to comprehend the exact mechanism of such a gene delivery system.…”
Section: Discussionmentioning
confidence: 99%
“…After 96 hours, absorbance was measured at 490 nm using CellTiter 96 ® AQueous Non-Radioactive Cell Proliferation Assay (Promega, Fitchburg, WI) in a Victor3 Multi Label Plate Counter (Perkin Elmer, Montreal, QC, Canada). 24 In a similar way, cardiomyocyte cell viabilities under oxidative stress in groups treated with different conditioned media were measured as described later in the study, using the same assay.…”
Section: Cell Proliferation and Viability Assaymentioning
confidence: 99%
“…The microencapsulated cells were cultured for 48 h in stationary flasks with standard medium, supplemented with antibiotics. The relative fluorescence units of each well containing 50 capsules resuspended in PBS were then measured using Victor3Multi Label Plate Counter (Perkin-Elmer, USA), as described elsewhere. , As shown in Figure A–D, the Bac MGFP -PAMAM (100) group showed significantly high normalized GFP expression (142.4 ± 16.8%) compared to Bac MGFP -PAMAM (10) (100 ± 7.5%) and Bac MGFP (33.6 ± 10.4%).…”
Section: Resultsmentioning
confidence: 99%
“…After 96 hours, absorbance was measured at 490 nm using CellTiter 96 ® AQueous Non-Radioactive Cell Proliferation Assay (Promega, Fitchburg, WI) in a Victor3 Multi Label Plate Counter (Perkin Elmer, Montreal, QC, Canada). 24 In a similar way, cardiomyocyte cell viabilities under oxidative stress in groups treated with different conditioned media were measured as described later in the study, using the same assay. The experiment was performed in triplicate.…”
Section: Cell Proliferation and Viability Assaymentioning
confidence: 99%